2017
DOI: 10.1002/aoc.3998
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural and DNA binding studies of mono‐ and dinuclear copper(II) complexes constructed with ─O and ─N donor ligands: Potential anti‐skin cancer drugs

Abstract: Mononuclear and dinuclear copper(II) complexes with thiophenecarboxylic acid, [Cu(3‐TCA)2(2,2′‐bpy)] (1), [Cu(3‐Me‐2‐TCA)2(H2O)(2,2′‐bpy)] (2), [Cu(5‐Me‐2‐TCA)2(H2O)(2,2′‐bpy)] (3) and [Cu2(2,5‐TDCA)(DMF)2(H2O)2(2,2′‐bpy)2](ClO4)2 (4) (where 3‐TCA = 3‐thiophenecarboxylic acid; 3‐Me‐2‐TCA = 3‐methyl‐2‐thiophenecarboxylic acid; 5‐Me‐2‐TCA = 5‐methyl‐2‐thiophenecarboxylic acid; 2,5‐TDCA = thiophene‐2,5‐dicarboxylic acid; 2,2′‐bpy = 2,2′‐bipyridyl; DMF = N,N‐dimethylformamide), were synthesized. Compounds 1–4 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that for other copper compounds tested on melanoma cells the reported IC 50 values were similar [ 39 , 40 , 41 ] or even higher [ 42 ] compared with the values found for complexes ( 1 ) and ( 2 ).…”
Section: Resultsmentioning
confidence: 56%
“…It is worth mentioning that for other copper compounds tested on melanoma cells the reported IC 50 values were similar [ 39 , 40 , 41 ] or even higher [ 42 ] compared with the values found for complexes ( 1 ) and ( 2 ).…”
Section: Resultsmentioning
confidence: 56%
“…For B16 cells, when treated with (2), the cell viability decreased to 5%, with IC 50 values of 6.88 µg/mL (7.6 µM) after 24 h treatment and 4.15 µg/mL (4.58 µM) after 48 h, respectively (Table 3). The ligand dmtp did not affect the viability of either BJ or B16 cells at 24 or 48 h. It is worth mentioning that for other copper compounds tested on melanoma cells, the reported IC 50 values were similar [35][36][37][38][39][40][41][42][43], and only one study reported lower values [38] compared with those found for complex (1).…”
Section: Biological Characterization 231 Cell Viability and Lactate Dehydrogenase Assaysmentioning
confidence: 95%
“…The Cu(II) systems represent beneficial species from this point of view, considering their reduced systemic toxicity [16]. Thus, several Cu(II) complexes were studied and proved to be as effective for melanoma treatment [18,29,[35][36][37][38][39][40][41][42][43]-some having, in addition, low toxicity on normal cells [18,29,[39][40][41][42][43].…”
Section: Biological Characterization 231 Cell Viability and Lactate Dehydrogenase Assaysmentioning
confidence: 99%
“…Other Cu(II) compounds active in the micromolar range on B16 melanoma cell lines have been developed based on pyrazole [19], pyridine [20][21][22], thiophenecarboxylato [23] derivatives, or even doxorubicin, a well-known organic-based antitumor drug [24].…”
Section: Introductionmentioning
confidence: 99%